2023
DOI: 10.3390/nursrep13010032
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use and Resilience: A Systematic Review and Meta-Analysis

Abstract: Problematic Internet use has become a major problem worldwide due to its numerous negative correlates in the field of health, both mental and physical, and its increasing prevalence, making it necessary to study both its risk and protective factors. Several studies have found a negative relationship between resilience and problematic Internet use, although the results are inconsistent. This meta-analysis assesses the relationship between problematic Internet use and resilience, and analyses its possible modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…A systematic review of moderating variables underlying the associations between screen media use and internalizing symptoms suggested that compared to other forms of screen media use, TV viewing was more weakly associated with internalizing symptoms [32]. The current findings can also be explained by protective factors associated with screen media use, such as resilience [33]. Another possible explanation is that the effects of screen media use on mental health problems might not be linear.…”
Section: Discussionmentioning
confidence: 55%
“…A systematic review of moderating variables underlying the associations between screen media use and internalizing symptoms suggested that compared to other forms of screen media use, TV viewing was more weakly associated with internalizing symptoms [32]. The current findings can also be explained by protective factors associated with screen media use, such as resilience [33]. Another possible explanation is that the effects of screen media use on mental health problems might not be linear.…”
Section: Discussionmentioning
confidence: 55%
“…In this sense, the COVID-19 restrictions may have prevented students living abroad from returning home, or students living with their parents from having a satisfying academic life in front of an uncertain future. In line with Hidalgo-Fuentes et al's [111] review, social factors, such as social support, are particularly important in addressing problematic technology use. In this distressing scenario, higher levels of PG may be explained by the need to regain some control over spatial movements-i.e., to reduce the distance from significant others-or to relieve emotional distress [6,112].…”
Section: Discussionmentioning
confidence: 79%
“…While Internet usage can reduce communication barriers, lower costs, enable rapid responses, and promote interpersonal bonds and social networks (Xie et al, 2021), maladaptive or excessive Internet use has been linked to adverse effects on mental health (Dahl D, 2020;Odacı & Çelik, 2013;Stepanikova, Nie, & He, 2010). Empirical evidence underscores that problematic Internet use (PIU) and Internet addiction (Dell'Osso B, 2021;Hidalgo-Fuentes S, 2023;KS, 1998;Lieberman, 2020;MM, 2014) increase the likelihood of depression, anxiety, social isolation, and even suicide (Cai Z, 2023;Haddad C, 2021;Kożybska, 2022;Lakkunarajah S, 2022;Marchant A, 2017;Peng C, 2021;Yang X, 2022).…”
Section: Introductionmentioning
confidence: 99%